2000
DOI: 10.1063/1.874034
|View full text |Cite
|
Sign up to set email alerts
|

Laser experiments to simulate supernova remnants

Abstract: An experiment using a large laser facility to simulate young supernova remnants ͑SNRs͒ is discussed. By analogy to the SNR, the laboratory system includes dense matter that explodes, expansion and cooling to produce energetic, flowing plasma, and the production of shock waves in lower-density surrounding matter. The scaling to SNRs in general and to SN1987A in particular is reviewed. The methods and results of x-ray radiography, by which the system in diagnosed, are discussed. The data show that the hohlraum u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In the past, the hohlraum was thought to couple energy to the target package only through the x rays, but discrepancies between data of recent long lived hydrodynamic experiments and simulations suggests otherwise. [5][6][7] Recent work has shown that by adding the effect of gold plasma pressure, simulations can be brought into agreement with the experimental data. 8 In this letter we report our work which involves modeling the effects of the hohlraum pressure and our success in resolving discrepancies between simulation and experimental results for the supernova remnant ͑SNR͒ experiment ͑Fig.…”
supporting
confidence: 61%
“…In the past, the hohlraum was thought to couple energy to the target package only through the x rays, but discrepancies between data of recent long lived hydrodynamic experiments and simulations suggests otherwise. [5][6][7] Recent work has shown that by adding the effect of gold plasma pressure, simulations can be brought into agreement with the experimental data. 8 In this letter we report our work which involves modeling the effects of the hohlraum pressure and our success in resolving discrepancies between simulation and experimental results for the supernova remnant ͑SNR͒ experiment ͑Fig.…”
supporting
confidence: 61%
“…However, current code capabilities do not enable adequate understanding of the many areas of physics that must be included in a full description due to the differing length-scales involved (Drake et al, 2000). To aid the understanding of the physics of some of these observations laboratory experiments have been conducted with the aim to reproduce the unstable blast wave structure which has been analytically predicted (Vishniac, 1983;Vishniac, 1991, 1987;Grun et al, 1991;Schappert et al, 1994).…”
mentioning
confidence: 97%
“…The interaction of the shock wave with structure in the experimental medium may produce dynamics of interest, for example, the destruction of material clumps. 20 Alternatively, the shock wave may act as an intermediate energy storage medium, permitting the generation of dynamic behavior over a longer interval 21,22 or even enable isentropic compression experiments that avoid further shock generation. 23 As the shock velocity u s increases, a shock wave in any medium will eventually become radiative.…”
Section: Strong Shocks and Radiative Shocksmentioning
confidence: 99%